Role of non-coding RNAs in age-related vascular cognitive impairment: An overview on diagnostic/prognostic value in Vascular Dementia and Vascular Parkinsonism. (October 2020) - Miceli, V.; Russelli, G.; Iannolo, G.; Gallo, A.; Lo Re, V.; Agnese, V.; Sparacia, G.; Conaldi, P.G.; Bulati, M.
Highlights: RNA-based epigenetic alterations have been related to cellular senescence in the pathogenesis of neurodegenerative diseases. ncRNAs could be involved in the pathogenesis of age-related neurovascular diseases. ncRNAs represent a new additional tool for clinicians to implement diagnosis and therapy in cognitive impairment pathologies. Abstract: Age is the pivotal risk factor for different common medical conditions such as cardiovascular diseases, cancer and dementia. Among age-related disorders, cardiovascular and cerebrovascular diseases, represent the leading causes of premature mortality strictly related to vascular ageing, a pathological condition characterized by endothelial dysfunction, atherosclerosis, hypertension, heart disease and stroke. These features negatively impact on the brain, owing to altered cerebral blood flow, neurovascular coupling and impaired endothelial permeability leading to cerebrovascular diseases (CVDs) as Vascular Dementia (VD) and Parkinsonism (VP). It is an increasing opinion that neurodegenerative disorders and cerebrovascular diseases are associated from a pathogenetic point of view, and in this review, we discuss how cerebrovascular dysfunctions, due to epigenetic alterations, are linked with neuronal degeneration/dysfunction that lead to cognitive impairment. The relation between neurodegenerative and cerebrovascular diseases are reviewed with a focus on role of ncRNAs in age-related vascular diseases impairing the endothelium in the blood–brain barrier with consequent dysfunction of cerebral blood flow. In this review we dissert about different regulatory mechanisms of gene expression implemented by ncRNAs in the pathogenesis of age-related neurovascular impairment, aiming to highlight the potential use of ncRNAs as biomarkers for diagnostic/prognostic purposes as well as novel therapeutic targets.